1997
DOI: 10.1006/nimg.1997.0298
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Localized Event-Related Optical Signals (EROS) in the Human Occipital Cortex: Comparisons with the Visual Evoked Potential and fMRI

Abstract: Localized evoked activity of the human cortex produces fast changes in optical properties that can be detected noninvasively (event-related optical signal, or EROS). In the present study a fast EROS response (latency approximately 100 ms) elicited in the occipital cortex by visual stimuli showed spatial congruence with fMRI signals and temporal correspondence with VEPs, thus combining subcentimeter spatial localization with subsecond temporal resolution. fMRI signals were recorded from striate and extrastriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 32 publications
5
81
1
1
Order By: Relevance
“…Near-infrared spectroscopy is able to measure hemodynamic, metabolic Heekeren et al, 1999), and fast neuronal responses to brain activation Gratton et al, 1997;Steinbrink et al, 2000;Wolf et al, 2002) with inexpensive and portable instrumentation. These capabilities are making NIRS, in its present technological state, an important tool in cognition and the neurosciences.…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared spectroscopy is able to measure hemodynamic, metabolic Heekeren et al, 1999), and fast neuronal responses to brain activation Gratton et al, 1997;Steinbrink et al, 2000;Wolf et al, 2002) with inexpensive and portable instrumentation. These capabilities are making NIRS, in its present technological state, an important tool in cognition and the neurosciences.…”
Section: Discussionmentioning
confidence: 99%
“…Photon delay increases (by a few picoseconds) when photons cross areas of the cortex that are active (for a review, see Fabiani, G. Gratton, & Corballis, 1996) with respect to the same areas when they are inactive. This technique has a high temporal resolution, comparable to that of ERPs, and a good spatial specificity, being able to localize cortical activity to within a few millimeters from corresponding fMRI recordings (Fabiani et aI., 1996;G. Gratton et al, 1997).…”
Section: Example 2 Bootstrap Analysis Of Peaks Of the Event-related Omentioning
confidence: 99%
“…It is a well-known phenomenon that the neuronal sources related to the early VEP components in response to the pattern-onset/ reversal visual stimulation correspond well to the activations in the human primary visual cortex (striate cortex or V1) acquired from fMRI (Di Russo et al, 2001;. Many studies have been performed to reveal the discrepancy between the fMRI loci at V1 and EEG or MEG source locations estimated from either dipole models (Gratoon et al, 1997;Roberts et al, 2000) or distributed source models (Moradi et al, 2003), and a large variation ranging from 5 mm to several cm has been observed in the previous studies.…”
Section: Introductionmentioning
confidence: 99%